NURSE BURNOUT PREDICTORS IN HEALTHCARE UNITS DURING COVID-19 IN EAST JAVA, INDONESIA - Windu Santoso; Sri Sudarsih (Indonesian Journal of Health Administration (Jurnal Administrasi Kesehatan Indonesia), 2023)
Background: As frontline health service providers, nurses are important in directly caring for patients during the COVID-19 pandemic. Nurses are very vulnerable to infection, and this causes ongoing anxiety and ultimately causes burnout. Aims: This study aims to identify factors that may lead to nurse burnout in various East Java healthcare facilities. Methods: This research used correlational analysis with a cross-sectional approach. The approach of purposive sampling was applied to select nurses from various health units in East Java with 200 respondents. The Maslach Burnout Syndrome Inventory-Human Services Survey (MBI-HSS) questionnaire was used for burnout variables and questionnaires for efficacy, job stress, and fear variables. Data analysis used multiple logistic regression with the ENTER method. Results: The findings indicated that the variable that had a significant relationship with burnout was work stress. The Odds Ratio (OR) analysis results for the job stress variable are 2.860, meaning that respondents who experience high job stress have a 3-fold risk of experiencing burnout compared to those who do not experience high stress. Conclusion: Job stress is predicted to be the most dominant variable causing burnout during the COVID-19 pandemic. Respondents with high job stress are more at risk of experiencing burnout. Keywords: burnout, COVID-19 pandemic, nurse